2014
DOI: 10.1038/nmat4140
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of an open-framework allotrope of silicon

Abstract: Silicon is ubiquitous in contemporary technology. The most stable form of silicon at ambient conditions takes on the structure of diamond (cF8, d-Si) and is an indirect bandgap semiconductor, which prevents it from being considered as a next-generation platform for semiconductor technologies. Here, we report the formation of a new orthorhombic allotrope of silicon, Si24, using a novel two-step synthesis methodology. First, a Na4Si24 precursor was synthesized at high pressure; second, sodium was removed from th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

24
290
1
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 260 publications
(316 citation statements)
references
References 37 publications
24
290
1
1
Order By: Relevance
“…Such irreversibility indicates a chance to synthesize new metastable forms by high-pressure modification. Quest for new forms of silicon is surged by photovoltaic application [31][32][33]. In order to achieve a better absorption in the visible light, the ideal material should have a direct band gap of 1-1.5 eV, and strong absorption within the solar spectrum.…”
Section: Decompression On Si-iimentioning
confidence: 99%
“…Such irreversibility indicates a chance to synthesize new metastable forms by high-pressure modification. Quest for new forms of silicon is surged by photovoltaic application [31][32][33]. In order to achieve a better absorption in the visible light, the ideal material should have a direct band gap of 1-1.5 eV, and strong absorption within the solar spectrum.…”
Section: Decompression On Si-iimentioning
confidence: 99%
“…However, when such guest atoms occupy the cages, they donate electrons to the framework making the material metallic and thus not useful for photovoltaic applications. Recently, Kim et al 26 reported the synthesis of a new Cmcm Si 24 allotrope free of metals, with open channels along the aaxis, formed from six and eight membered sp 3 silicon rings, and with a quasi-direct band gap of 1.3 eV. Baranowski and coauthors 24 successfully synthesized a type-II Si-Ge clathrate alloy.…”
Section: Introductionmentioning
confidence: 99%
“…Electronic structure calculations 5,6 also suggested the band gap of Si clathrate is either direct or quasi-direct (namely, formally indirect, but the direct and indirect gaps are nearly degenerate). A recently synthesized new allotrope of silicon, Si 24 , was identified to possess an orthorhombic lattice and to contain eight-membered rings 7 . Both experimental measurements and theoretical calculations suggested Si 24 has a quasi-direct band gap of 1.3 eV.…”
mentioning
confidence: 99%